Reassessing Reductionism in Logical Positivism: A Dogmatic Legal Critique - Annas, Gilang Kresnanda; Kurniyanto, M. Nurlaili Dwi; Yandy, Eza Tri; Fatiha, Nilam (UIN Sunan Kalijaga Yogyakarta, 2025)
Despite its long-standing dominance in dogmatic legal science, logical positivism has been increasingly criticized for its tendency to reduce law to a purely normative and formal system. While extensive scholarship has examined legal positivism in general, the specific problem of reductionist assumptions within logical positivism—and their implications for dogmatic legal science—remains insufficiently explored. This article aims to critically examine the reductionist assumptions underlying logical positivism from the perspective of dogmatic legal science, with particular attention to their epistemological consequences. This study adopts a normative–doctrinal legal method combined with conceptual and critical approaches to analyze the epistemological foundations of reductionism in logical positivism. The analysis draws on legal positivist theory and its critiques, particularly dogmatic legal theory and critical jurisprudence, to assess the limitations of reductionist reasoning in legal analysis. The study finds that reductionist assumptions in logical positivism significantly limit the capacity of dogmatic legal science to account for the social, moral, and interpretative dimensions of law, thereby narrowing its epistemological scope. This article contributes to legal theory by demonstrating the need for a more context-sensitive and interdisciplinary framework within dogmatic legal science to overcome the epistemological limitations of logical positivism.